2021
DOI: 10.3390/s21092983
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive Sensors for the Assessment of Older Adult’s Frailty: A Scoping Review

Abstract: Ubiquity (devices becoming part of the context) and transparency (devices not interfering with daily activities) are very significant in healthcare monitoring applications for elders. The present study undertakes a scoping review to map the literature on sensor-based unobtrusive monitoring of older adults’ frailty. We aim to determine what types of devices comply with unobtrusiveness requirements, which frailty markers have been unobtrusively assessed, which unsupervised devices have been tested, the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
(601 reference statements)
0
1
0
1
Order By: Relevance
“…In particular, it was found [29] that older EUs perceive a greater value in technology when it positively impacts their health and well-being in addition to its perceived usefulness [65]. However, digital devices should be placed in an unobtrusive manner; that is, they should require little attention in the EUs' daily lives, resulting in better acceptance [69][70][71]. Moreover, our ICs reported that they would greatly appreciate having tools with GPS available to track the location of PwD.…”
Section: Overall Technology and The Demicare Integrated System: The P...mentioning
confidence: 92%
“…In particular, it was found [29] that older EUs perceive a greater value in technology when it positively impacts their health and well-being in addition to its perceived usefulness [65]. However, digital devices should be placed in an unobtrusive manner; that is, they should require little attention in the EUs' daily lives, resulting in better acceptance [69][70][71]. Moreover, our ICs reported that they would greatly appreciate having tools with GPS available to track the location of PwD.…”
Section: Overall Technology and The Demicare Integrated System: The P...mentioning
confidence: 92%
“…New technologies have been proposed for early screening of frailty, including the use of wearable sensors that can help monitor the risk of developing frailty in the older adult population [7][8][9][10] . A systematic review 11 which included 29 observational studies involving older adults who used wearable sensors to identify the presence of frailty and pre-frailty highlighted the heterogeneity of the parameters examined in relation to identifying frailty and the body locations used.…”
Section: Introductionmentioning
confidence: 99%
“…Novas tecnologias têm sido propostas para o rastreio precoce da fragilidade, dentre elas, o uso de sensores vestíveis que podem auxiliar na monitorização do risco de desenvolvimento de fragilidade na população idosa [7][8][9][10] . Uma revisão sistemática 11 incluiu 29 estudos observacionais envolvendo idosos que utilizaram sensores vestíveis para identificar a presença de fragilidade e préfragilidade.…”
Section: Introductionunclassified